Modelling of disordering regions in proton-irradiated silicon. (May 2020) - Bogatov, N; Grigoryan, L; Klenevsky, A; Kovalenko, M; Nesterenko, I
Abstract: A model of disordering regions generation as a result of interstitial atom-vacancy pairs separation in view of neutral and charged pair states was developed. The model allows to define the radius and the mean number of vacancies of a disordering region. Distribution profiles of interstitial silicon, vacancies, divacancies, disordering regions created by low-energy protons in silicon were calculated, as well as the disordering regions parameters dependencies on proton energies. It was shown that the disordering region distribution maximum is spatially separated from interstitial silicon, vacancies and divacancies distribution maximums. This allows to differentially modify superficial and volumetric properties of semiconductor structures.